Motivation and participation in multi-stakeholder innovation platforms in the Great Lakes Region of Africa - Mulema, Annet A.; Mazur, R.E. (Oxford University Press, 2016)
The relationship between motivation and participation in five agricultural research and development innovation platforms (IPs) in Africa’s Great Lakes Region is examined. We analyze data from surveys and in-depth interviews, and focus group discussions. Although farmers prioritized new knowledge and skills, these were not sufficient to consistently foster active participation. Anticipated economic (markets, income, and credit) and material (agricultural inputs) livelihood benefits did encourage active farmer participation. Few actors mentioned social incentives (network connections and status) as motivating factors. Participation of local policy makers and the private business sector was limited. Overall, participation was curtailed by unfulfilled expectations of tangible immediate benefits, limited understanding of the IP concept, lack of resources, and prior commitments.